HUBUNGAN KARAKTERISTIK INDIVIDU DAN RIWAYAT PENYAKIT DENGAN NILAI AMBANG DENGAR POLISI LALU LINTAS SUBUNIT PATWAL KOTA SEMARANG - Sandyasti, Laksnita Kumara; Setyaningsih, Yuliani; Ekawati, Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
The increasing number of vehicles and the permanent number of streets resulted in increasing levels of traffic noise. Patwal traffic police has the main task to resolve the traffic jam. Patwal traffic policemen have hearing loss risk that indicated by the increase of the hearing threshold value. This study aims to analyze the relationship of age, work period, hobbies, history of hypertension, diabetes mellitus, and the degree of smoking to the hearing threshold value of Patwal traffic policemen in Semarang City. The type of research used is analytical with cross sectional method. The samples used in this study were 34 Patwal traffic policemen. The data were taken with audiometry test and questionnaire. Based on the analysis using Chi-Square test, it can be concluded that the variables related to hearing threshold value are working period (p = 0,004) and smoking degree (p = 0,026). While unrelated variables were age, hobby, history of diabetes mellitus, and history of hypertension. It can be concluded that work period and degree of smoking are related to hearing threshold value of Patwal traffic policemen of Semarang City.